Relations between humans and non-humans in Amazigh North African oral literature - Anna Maria di Tolla (Tydskrif vir letterkunde, 2025)
In this article, I examine the representation of environmental issues in Amazigh narratives. I focus on texts that address the relationships between humans, society, the environment, and colonial greed. Employing ecocritical theory, I offer an interpretation of Amazigh oral traditions and storytelling, highlighting the vital role that autochthonous peoples play in environmental stewardship and sustainable development through their traditional practices. The interdisciplinary approach I adopt to analyse the material draws on ecocriticism—a literary and ethical approach to the environment—as well as elements of cultural and folklore studies. After providing an overview of the environmental challenges faced by Western societies in the 19th century and the ways in which they were conceptualised, I introduce the perspectives found in selected examples of Amazigh oral literature that engage with environmental concerns arising from industrialisation, technicism, and colonialism. My analysis of Amazigh tales involving animals and natural elements is enriched by comparisons with animals in the broader Maghrebi tradition, as well as parallels with Dogon myths and narratives from Sahelian-Sudanese ethnic groups. These comparisons help to deepen our understanding of Amazigh cosmologies and verbal systems.